Sixteen teachers teaching: two-year college perspectives - Patrick, Sullivan, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2020)
A personal tour of classrooms and teaching practices of sixteen distinguished two-year college English teachers and frames the teachers, students, and administrators work as a matter of social justice and brings together first-hand examples from teachers who translate experience into practical classroom strategies.--Provided by publisher.
16 teachers teaching: two-year college perspectives
Dispatches from bartertown: building pedagogy in the exigent moment / Darin Jensen -- Teaching as celebration: an interview with Helane Adams Androne / Helane Adams Androne -- Flexibility / Bridgette Stepule -- Encouragement / Lydia Sekscenski -- Compassionate writing instruction / Brett Griffiths -- The theory that remains: toward a theoretically informed writing assignment / Jeff Klausman -- Find a practice that will sustain you: an interview with Jeffrey Andelora / Jeffrey Andelora -- Potential / Darlene Pierpont -- Mindfulness / Kevin Rodriguez -- Social justice and the two-year college: cultivating critical information literacy skills in first-year writing / Holly Hassel -- Community / Lauren Sills -- Inversive teaching / Hope Parisi -- The risky business of engaging racial equity in writing instruction: a tragedy in five acts, with a new postscript written for this volume / Taiyon J. Coleman, Renee DeLong, Kathleen Sheerin DeVore, Shannon Gibney, and Michael C. Kuhne -- Setting students up for success: teaching the Accelerated Learning Program (ALP) / Jamey Gallagher -- Second chance pedagogy: integrating college-level skills and strategies into a developmental writing course / Joanne Baird Giordano -- Real life / Jamil Shakoor -- Pedagogical evolution: how my teaching has changed in ten years of the Accelerated Learning Program (ALP) / Peter Adams -- For new English teachers / Leah McNeir -- A path to citizenship: an interview with Howard Tinberg.
Keywords: Composition (Language arts) -- Study and teaching (Higher); English language -- Rhetoric -- Study and teaching (Higher); Community college teachers; Community colleges; Junior colleges